Simulación avanzada del desempeño de vehículos automotores híbridos utilizando biocombustibles (2020)
This work evaluated the emissions generated by the operation of two motor vehicles through the Advanced Vehicle Simulator (ADVISOR ®), an advanced simulator for vehicles using MATLAB as a base of execution, these vehicles followed the route of line 1 of the Mexican City Public Passenger Transport Corridor System better known as Metrobus, Indians Verdes – Dr. Gálvez. The vehicles were: the Volvo® 7700 hybrid model that is used by Metrobús and the Toyota® Prius 2004, being chosen these models for being representative hybrid passenger transport in the vehicle park of Mexico City. By the nature of the engines, biodiesel was chosen as fuel in the case of the Volvo® and bioethanol model in the case of the Toyota® model. The work made it possible to evaluate the generation of polluting emissions using these biofuels, as well as the performance of vehicles to propose a solution to Mexico City's environmental pollution problems.